2005
DOI: 10.4049/jimmunol.175.3.1758
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisRegulates CD1 Antigen Presentation Pathways through TLR-2

Abstract: Mycobacterium tuberculosis remains a major pathogen of worldwide importance, which releases lipid Ags that are presented to human T cells during the course of tuberculosis infections. Here we report that cellular infection with live M. tuberculosis or exposure to mycobacterial cell wall products converted CD1− myeloid precursors into competent APCs that expressed group 1 CD1 proteins (CD1a, CD1b, and CD1c). The appearance of group 1 CD1 proteins at the surface of infected or activated cells occurred via transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 69 publications
6
115
1
2
Order By: Relevance
“…Although this result has to be confirmed experimentally, it suggests that DMAG could also modulate the effectiveness of lipidic antigen presentation to natural killer T cells. In agreement with our results, Roura-Mir et al (76) previously demonstrated that the mycobacterial cell wall lipids of M. tuberculosis that activate human monocytes through TLR2 up-regulated CD1a, CD1b, and CD1c gene and protein expression, whereas CD1d transcripts decreased on the first day after exposure to the lipids.…”
Section: Discussionsupporting
confidence: 82%
“…Although this result has to be confirmed experimentally, it suggests that DMAG could also modulate the effectiveness of lipidic antigen presentation to natural killer T cells. In agreement with our results, Roura-Mir et al (76) previously demonstrated that the mycobacterial cell wall lipids of M. tuberculosis that activate human monocytes through TLR2 up-regulated CD1a, CD1b, and CD1c gene and protein expression, whereas CD1d transcripts decreased on the first day after exposure to the lipids.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, TLR-2 and TLR-4 are important to control infection (Reiling et al, 2002) and mycobacterial lipids are known to be ligands for TLRs, triggering production of IL-12 and other factors. As suggested by Roura-Mir et al (2005), mycobacterial cell wall lipids may provide two distinct signals. One signal may lead to the activation of lipid-reactive T cells while the other may act as a lipid adjuvant to activate antigen-presenting cells through TLR-2.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike virus infection and viral pathogen-associated patterns, treatment of DC with nonviral TLR ligands (LPS, zymosan) strongly decreased the number of CD1D mRNA transcripts. Others have shown diminished CD1D mRNA expression in monocytes exposed to Mycobacterium tuberculosis lipids [58]. Accordingly, LPS-treated DC produced lower amounts of the CD1d heavy chain (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…Others have shown diminished CD1D mRNA expression in monocytes exposed to Mycobacterium tuberculosis lipids [58]. Accordingly, LPS-treated DC produced lower amounts of the CD1d heavy chain (data not shown).…”
Section: Discussionmentioning
confidence: 66%